What is the best internal fixation in pelvic fracture models with open-book injury and anterior sacroiliac joint disruption? - Ismail H. Dilogo (Medical Journal of Indonesia, 2015)
Background: The best operative management for open-book pelvic injury with anterior sacroiliac disruption (OTA/AO B1.1 classification) is still debated. This biomechanical study aimed to find the best internal fixation technique for such injury.